RELAGH - the challenge of having a scientific network in Latin America: an account from the presidents - Rojas Martínez, Augusto; Giraldo Ríos, Alejandro; Jiménez Arce, Gerardo; Falcón de Vargas, Aída; Giugliani, Roberto (2014)
Latin America and the Caribbean region make up one of the largest areas of the world, and this region is characterized by a complex mixture of ethnic groupss haring Iberian languages. The area is comprised of nations andregions with different levels of social development. This region has experienced historical advances in the last decades to increase the minimal standards of quality of life; however, several factors, such as concentrated populations in large urban centers and isolated and poor communities, still have an important impact on medical services,particularly genetic sservices. Latin American researchers have greatly contributed to the development of human genetics and historic inter-ethnic diversity, and the multiplicity of geographic areas are unique for the study of gene-environment interactions. As a result of regional developments in the fields of human and medical genetics, the Latin American Network of Human Genetics (Red Latinoamericana de Genética Humana - RELAGH) was created in 2001 to foster the networking of national associations and societies dedicated to these scientific disciplines. RELAGH has developed important educational activities, such as the Latin American School of Human and Medical Genetics (ELAG), and has held three biannual meetings to encourage international research cooperation among the member countries and international organizations. Since its foundation,RELAGH has been admitted as a full regional member to the International Federation of Human Genetics Societies. This article describes the historical aspects, activities, developments, and challenges that are still faced by the Network.